Rekonstruksi Pembelajaran Matematika di Era Revolusi Industri 4.0 - Sumaryanta Sumaryanta; Agus Dwi Wibawa (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2020)
The 4th industrial revolution demands and encourages the educational reformation in many countries, including Indonesia. The rapid changes caused by the emergence of the 4th industrial revolution require adjustments in various aspects of life, including education. Mathematics education as the key component of the education system in Indonesia should be adapted to answer the challenge of the student’s needs in line with the dynamics changes at the 4th industrial revolution era. Mathematical renewal and updates is a necessity, essential and urgent point to execute. The mathematics teaching and learning should be designed and implemented to prepare new generation facing continuous uncertainty and alteration. This article is intended to present a new perspective on the reconstruction of mathematics teaching and learning in the era of the 4th industrial revolution. This article, as well, is expected to provide a new paradigm in viewing and organizing mathematics teaching and learning amidst the current changes in the 4th industrial revolution era.